Analysis of The Prospects for The Implementation of The Customary Land Registration System: Benefits and Legal Issues - Salam, Safrin; Sari, Rizki Mustika; Nurcahyo, Edy; Izu, Cynthia C.; Syahrul; Tonny, Fajrin (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
The existence of Permen ATR/KBPN No. 14 of 2024 regulates the customary land registration system in Indonesia. The purpose of this research is to analyses the customary land registration system and conceptually analyses the legal certainty of the issuance of customary land certificates. This type of research is normative legal research. The approaches used in analyzing in this research are legislative approach, case approach and concept approach. The results showed that the customary land registration system has been regulated in Permen ATR / KBPN No. 14 of 2024, in this legal provision it is regulated that customary land can be controlled in the form of management rights decisions and property rights certificates while the legal certainty of the issuance of customary land certificates according to Permen ATR / KBPN No. 14 of 2024 still encounters problems in terms of legal concepts.